(untitled) (Eurasian Medical Research Periodical, 2022)
This article discusses recurrent schizophrenia or schizoaffective psychosis. This we must know as the source of future ideas about schizoaffective psychosis and true recurrent schizophrenia. But just citing it as a source is not enough. The fact is that in the late XIX - early XX centuries. there were fierce disputes and discussions, attempts to distinguish between periodic psychoses and manic-depressive ones. These efforts have continued to this day. The names have changed, but the essence has not changed.